HTML : the definitive guide - Musciano, Chuck (Nutshell handbook., 1997)
The authors cover every element of HTML in detail, explaining how each element works and how it interacts with other elements, and provide hundreds of examples as models for writing your own effective Web pages and mastering advanced features.